Consumer awareness and knowledge regarding use of non-steroidal anti-inflammatory drugs (NSAIDs) in a metropolitan area - Montuori, Paolo; Shojaeian, Seyedeh Zahra; Pennino, Francesca; D’Angelo, Daniela; Sorrentino, Michele; Di Sarno, Salvatore; Nubi, Raffaele; Nardo, Alfonso; Triassi, Maria (Frontiers in Pharmacology, 2024)
Background: Non-steroidal anti-inflammatory drugs (NSAIDs) have well-known adverse effects. Numerous studies have shown inappropriate behaviors regarding the use of NSAIDs. The key aim of this study is to analyze simultaneously knowledge, attitudes, and behaviors regarding the use of NSAIDs in one of the largest and populous areas of Italy, Naples. Methods: From 2021 December 14th to 2022 January 4th, a cross sectional survey study was conducted using a snowball sampling method among community centers, working places and universities. In order to be included in the study, participants were required to be 18 years or older and be residents in the metropolitan area of Naples. Three Multiple Linear Regression Analysis (MLRA) were developed including those variables that were potentially associated with the following outcomes of interest: Knowledge (Model 1), Attitudes (Model 2) and Behaviour regarding organ donation (Model 3). Results: The data acquired from 1012 questionnaires -administered to subjects evenly divided by gender and with an average age of 36.8 years -revealed that only 7.9% of participants say they do not take NSAIDs, while half of the participants (50%) admitted to occasionally take them. The results show a statistically significant correlation between attitudes regarding the appropriate use of NSAIDs and less knowledge. The regression analysis indicated that behaviors regarding the appropriate use of NSAIDs were statistically significant in younger age respondents, in non-smokers and surprisingly in those with no children. The very interesting result, carried out by the regression analysis, is that behaviors regarding the appropriate use of NSAIDs were significantly higher among respondents with less knowledge and positive attitudes.According to the collected data and statistical analysis, it is possible to identify factors that can greatly affect the inappropriate behaviors regarding the use of NSAIDs and establish targeted prevention programs.